Efficacy of exercise protocols on balance in badminton players -a systematic review & meta-analysis - Indora, N. K.; Manoj, M.; Jaspreet, K. (Central European Journal of Sport Sciences and Medicine, 2022)
Objective. the goal of this "systematic review" and meta-analysis is to find out the efficacy of exercise regimes on balance in badminton players. Study design. Systematic review and meta-analysis. data Source. Pub Med, "Cochrane database (Cochrane Central register of controlled Trials)", google Scholar, Springer, and DoAJ. Eligibility criteria. limits were applied to database searches to identify papers published in English and only human studies were included. results. result of Meta - analysis was statistically significant in "anterior component of Y-balance test" (MD = 2.39, 95% ci = 1.90, 2.89; "p = 0.00001") with low heterogeneity (i2 = 0%, p < 0.41). There was statistically significant improvement in postero-medial component of y- balance (MD = 2.87, 95% ci = 0.55, 5.19; p = 0.02) with "moderate heterogeneity" (i2 = 39%, p < 0.19). result showed statistically significant improvement in postero-lateral component of y- balance test (MD = 3.09, 95% ci = 0.64, 5.65; p = 0.02) with "moderate heterogeneity (i2 = 38%, p < 0.20)". There was "statistically significant "improvement in overall balance of y-balance test in "experimental group as compared to control group (MD = 8.49, 95% ci = 4.62,12.36; p = 0.0001) with low heterogeneity (i 2 = 0%, P < 0.47)". Conclusion. this systematic and meta-analysis concluded that various exercise protocols may result in improvement in the balance of badminton players.